Barriers to Access to Treatment for Mothers with Postpartum Depression in Primary Health Care Centers: A Predictive Model [Barreiras de Acesso a Tratamento Para Mães Com Depressão Pós-Parto Em Centros de Atenção Primária: Um Modelo Preditivo] [Barreras de Acceso a Tratamiento de Madres Con Depresión Posparto en Centros de Atención Primaria: Un Modelo Predictive] - Martinez-Diaz, P (University of Sao Paulo, Ribeirao Preto College of Nursing Organisation, 2016)
Objective: to develop a predictive model to evaluate the factors that modify the access to treatment for Postpartum Depression (PPD). Methods: prospective study with mothers who participated in the monitoring of child health in primary care centers. For the initial assessment and during 3 months, it was considered: sociodemographic data, gyneco-obstetric data, data on the services provided, depressive symptoms according to the Edinburgh Postpartum Depression Scale (EPDS) and quality of life according to the Short Form-36 Health Status Questionnaire (SF- 36). The diagnosis of depression was made based on MINI. Mothers diagnosed with PPD in the initial evaluation, were followed-up. Results: a statistical model was constructed to determine the factors that prevented access to treatment, which consisted of: item 2 of EPDS (OR 0.43, 95%CI: 0.20-0.93) and item 5 (OR 0.48, 95%CI: 0.21-1.09), and previous history of depression treatment (OR 0.26, 95%CI: 0.61-1.06). Area under the ROC curve for the model=0.79; p-value for the Hosmer-Lemershow=0.73. Conclusion: it was elaborated a simple, well standardized and accurate profile, which advises that nurses should pay attention to those mothers diagnosed with PPD, presenting low/no anhedonia (item 2 of EPDS), scarce/no panic/fear (item 5 of EPDS), and no history of depression, as it is likely that these women do not initiate treatment. © 2016 Revista Latino-Americana de Enfermagem.